2018
DOI: 10.1007/s40261-018-0671-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatitis B Reactivation in Patients with Psoriasis on Ustekinumab

Abstract: The study outcomes indicate that ustekinumab could be safe for psoriasis patients since none developed persistent hepatitis or acute liver failure during therapy. However, the re-appearance of plasma HBV DNA requires appropriate monitoring of HBV viral load during ustekinumab treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 45 publications
2
25
0
3
Order By: Relevance
“…It is recommended to treat patients for active or latent TB prior to the onset of therapy. Limited data show that ustekinumab treatment in patients with active or latent hepatitis B virus or hepatitis C virus is safe and effective and is not associated with an increased rate of reactivation [114][115][116].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to treat patients for active or latent TB prior to the onset of therapy. Limited data show that ustekinumab treatment in patients with active or latent hepatitis B virus or hepatitis C virus is safe and effective and is not associated with an increased rate of reactivation [114][115][116].…”
Section: Discussionmentioning
confidence: 99%
“…Binds to and neutralizes interleukin 12 and 23, which may be required for T cell activation and/ or proliferation High (B) [135][136][137] Moderate (B) 137 Calcineurin inhibitors Ciclosporin, tacrolimus Solid organ transplantation, rheumatoid arthritis, psoriasis, aplastic anemia Inhibit calcineurin which is required for signal transduction of T cell activation, and suppress transcription of IL-2 which is required for T cell proliferation Low (C) 138 139 Low (C) 140 Mammalian target of rapamycin (mTOR) inhibitors Everolimus Breast cancer, renal cell carcinoma, neuroendocrine tumors Block T and B cell proliferation by inhibiting the response to growth factors Unclassifiable (D) 141 142 Data not available Chemokine inhibitors…”
Section: Ustekinumab Psoriasis and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…A total of 32 studies were identified evaluating immunosuppressing biologics and other disease-modifying antirheumatic drugs (DMARDs) for autoimmune diseases, which included rheumatoid arthritis, psoriasis, systemic lupus erythematosus, and aplastic anemia (Table 4). 67-98 TNFα inhibitors were the most common agents evaluated, and 6 studies included rituximab. Use of prophylaxis was rare.…”
Section: Resultsmentioning
confidence: 99%